2017
DOI: 10.14295/cs.v7i4.1579
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade pós-colheita de maracujá-amarelo em função de porta-enxertos e ambientes de cultivo

Abstract: Objetivou-se avaliar a influência de porta-enxertos e ambientes nas características físico-químicas de frutos de maracujazeiros. O experimento foi instalado e conduzido em duas propriedades no município de Terra Nova do Norte, Mato Grosso. Adotou-se o esquema fatorial 2 × 8, no delineamento de blocos casualizados, com quatro repetições, sendo dois ambientes de produção (Ambiente 1 e Ambiente 2) e sete porta-enxertos, além da testemunha. Foram utilizados os portaenxertos dos seguintes genótipos: CPAC M5-H-67, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
(11 reference statements)
0
2
1
2
Order By: Relevance
“…The higher contents of soluble solids in the composition of the fruits increased the industry yield since the higher is the concentration of TSS, the lower will be the number of fruits used to obtain the pulp in the preparation of the concentrated juice, being necessary 11 kg of fruits with TSS between 11 and 12 ºBrix to obtain 1 kg of concentrated juice at 50 ºBrix . The ratio value (Table 1) was lower (p<0.05) than the 3.95 and 4.01 values found by Botelho et al (2016) and Negreiros et al (2008), respectively. The low TSS/ TTA relation occurred as a consequence of the high acidity content, which, according to Aguiar et al (2017) and Vianna-Silva et al (2008), may undergo variation as a function of the temperature, water demand, and cultivation practices, directly reflecting on the ratio value.…”
Section: Resultscontrasting
confidence: 54%
“…The higher contents of soluble solids in the composition of the fruits increased the industry yield since the higher is the concentration of TSS, the lower will be the number of fruits used to obtain the pulp in the preparation of the concentrated juice, being necessary 11 kg of fruits with TSS between 11 and 12 ºBrix to obtain 1 kg of concentrated juice at 50 ºBrix . The ratio value (Table 1) was lower (p<0.05) than the 3.95 and 4.01 values found by Botelho et al (2016) and Negreiros et al (2008), respectively. The low TSS/ TTA relation occurred as a consequence of the high acidity content, which, according to Aguiar et al (2017) and Vianna-Silva et al (2008), may undergo variation as a function of the temperature, water demand, and cultivation practices, directly reflecting on the ratio value.…”
Section: Resultscontrasting
confidence: 54%
“…A garantia de origem é um pré-requisito básico para importar e os frutos devem ter qualidade sanitária, no que diz respeito a contaminantes biológicos e resíduos químicos. Dentre os fatores que colocam a fruta com baixa credibilidade diante dos mercados internacionais são injurias causadas por doenças graves que afetam a cultura do maracujazeiro, inviabilizando a sua produção sob o ponto de vista econômico, fazendo com que ela adquira caráter itinerante (BOTELHO et al, 2016). A região central brasileira compreendendo os estados de Mato Grosso do Sul, Mato Grosso, Goiás, Tocantins, Minas Gerais e o Distrito Federal, também vem optando pela fruticultura, na crista da onda diversificadora que varre o país e, dentro dela, está o maracujazeiro, que vem se constituindo uma opção importante (RUGGEIRO, 1998).…”
unclassified
“…Silva et al (2016a), found values of 12.9 °Brix for fruits of yellow passion fruit. It is known that the environment where the fruits are produced influence some characteristics of fruit quality, such as the soluble solids content (Botelho et al, 2016).…”
Section: Resultsmentioning
confidence: 99%